2024
DOI: 10.3390/audiolres14010007
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children Affected by Single-Sided Deafness: A Comprehensive Review

Giuseppe Santopietro,
Virginia Fancello,
Giuseppe Fancello
et al.

Abstract: Children with single-sided deafness (SSD) may experience delays in language and speech development. Reduced speech discrimination and poor sound localization abilities in young SSD patients may result in greater cognitive efforts required to focus and process auditory information, as well as increased listening-related fatigue. Consequently, these children can have a higher risk of academic failure and are often in need of extra help at school. Recently, cochlear implants (CIs) have been introduced as a rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Currently, published evidence and clinical experience confirm the crucial role of the timely diagnosis and treatment of UHL in improving linguistic, cognitive, socio-emotional, and communicative development [ 15 ]. Although the treatment of USNHL is still controversial, recent comprehensive reviews have suggested that, in selected cases, cochlear implantation for children with SSD can lead to significant improvements in overall hearing outcomes [ 18 , 19 ]. The aim of this study was to evaluate the audiological characteristics (degree of HL, affected side, audiometric configuration, and hearing outcomes), adherence to treatment (hearing aid or cochlear implant), causes of HL, and parents’ opinions on hearing device use in children aged 6 to 12 years with USNHL who attended our tertiary-level referral audiologic center.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, published evidence and clinical experience confirm the crucial role of the timely diagnosis and treatment of UHL in improving linguistic, cognitive, socio-emotional, and communicative development [ 15 ]. Although the treatment of USNHL is still controversial, recent comprehensive reviews have suggested that, in selected cases, cochlear implantation for children with SSD can lead to significant improvements in overall hearing outcomes [ 18 , 19 ]. The aim of this study was to evaluate the audiological characteristics (degree of HL, affected side, audiometric configuration, and hearing outcomes), adherence to treatment (hearing aid or cochlear implant), causes of HL, and parents’ opinions on hearing device use in children aged 6 to 12 years with USNHL who attended our tertiary-level referral audiologic center.…”
Section: Introductionmentioning
confidence: 99%